Investigation of Nutritional Knowledge Levels and Attitudes Towards Doping of Amateur and Professional Athletes - Nihal AKOĞUZ YAZICI; Esranur TERZİ; Can AKYILDIZ (ümit doğan üstün, 2024)
This study aimed to establish the correlation between the nutritional knowledge levels of amateur and professional athletes and their attitudes towards doping. Additionally, it sought to analyze these relationships in relation to relevant variables. The study included a sample group of 141 amateur athletes and 57 professional athletes, resulting in a total of 197 athletes. The average age of the participants was 21.60±6.89 years. The study's data were gathered through online means, utilizing the Athlete Nutrition Knowledge Scale and Attitude Towards Doping Scale. The data that followed a normal distribution was analyzed using the Independent T-Test, One-Way Anova, and Pearson Correlation test. According to the analyzed results, there were no significant differences in attitude levels towards doping based on gender, sport branch, sport history, and age (p>0.05). However, there was a significant difference in attitude levels based on educational status (p<0.05). Furthermore, although there were no significant differences in nutritional knowledge levels based on gender and sport branch (p>0.05), there were significant differences based on educational status, sport history, and age (p<0.05). Furthermore, there was no substantial correlation observed between the attitude towards doping and the level of nutritional knowledge (p>0.05). These findings can provide insights into the correlation between athletes' understanding of nutrition and their inclination towards doping, contributing to a deeper understanding of this matter.